Colliers and Christianity: religion in the coalmining communities of South Wales and the East Midlands c1860 to 1930s with a particular focus on the Rhondda Valleys in South Wales and the Hucknall and Shirebrook areas in Nottinghamshire and Derbyshire - Kidger, Margaret Eleanor (2012)
Many studies that have examined the issues of ‘secularisation’ and ‘religion and the working class’ have been based on large cities. This study, after first reviewing the debate on these issues, looks at institutional religion in coalmining communities in the East Midlands and South Wales from 1860 to the 1930s. It focuses particularly, though not exclusively, on Hucknall and Shirebrook in the East Midlands and the Rhondda Valleys in South Wales. The difficulties faced by the churches in providing for the needs of the rapidly growing mining communities are then outlined; the progress made by Nonconformity, Anglicanism and Roman Catholicism is examined and the contribution that the churches made to the lives of both church members and communities is assessed. The study also looks at the contribution of the miners themselves to institutional religion. The final chapter focuses on the inter-war years and assesses possible reasons for the widespread decline in religious commitment during that period and in so doing examines the extent to which the churches themselves may have inadvertently contributed to their own decline. Overall this study argues that institutional religion made a significant contribution, at least until 1914, to the life of the mining communities. It was mainly in the interwar period that, for a variety of reasons, secularisation in these working class communities increased.